The Influence of Social Media on Gen Z Consumer Behavior in E-Commerce - Dima, Javiardi; Sogen, Maria Magdalena Beatrice; Tallo, Clerinzia Gladista; Ndun, Riandri; Taneo, Rizaldy Evander (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study investigates the influence of social media content on Gen Z students' purchasing decisions in e-commerce. The problem is how significantly social media—through promotional content, influencers, and short videos—affects the behavior of Gen Z consumers. Using a descriptive quantitative method, data were collected from 30 students at Universitas Citra Bangsa using a closed-ended questionnaire. The results indicate that 86.6% of students use social media frequently, 70% often see promotional content, and 50% are influenced by short-form videos and testimonials. The findings confirm that decision-making is shaped by engaging and trustworthy content, such as influencer recommendations and viral trends. Thus, social media plays a central role in shaping purchasing behavior among Gen Z students.